Preparation And Characterization Of Phase Inversion Poly (Vinyl Alcohol)/ Multi-Walled Carbon Nanotubes Dye Removal Adsorbents - Mohamad Anuar, Siti Aisyah (Universiti Sains Malaysia, 2018)
Textile industries produce a lot of wastewater which contains a significant number of pollutants, including dyes such as methylene blue. Engineered adsorptive materials having inorganic constituent incorporated polymeric matrix provide the possibility of removing a wide range of pollutants. In this study, poly (vinyl alcohol)/ multi-walled carbon nanotubes adsorbents were prepared via phase inversion process. Adding multi-walled carbon nanotubes which is a typical mesoporous material with average pore diameter of 3.4 nm to the poly (vinyl alcohol) adsorbents provided a microporous and asymmetric structure for the adsorptive adsorbents in methylene blue dye removal. In order to find the optimum condition, the adsorption capacity was examined at various operating parameters, such as initial concentration, contact time and adsorbent dosage. The adsorption capacity of 0.068 mg/g and the highest removal efficiency of 56.21 % were obtained at initial dye concentration of 2.00 mg/L at 4 hours adsorption time by applying 1.00 g of poly (vinyl alcohol)/ multi-walled carbon nanotubes adsorbents. The experimental data were fitted well with the Freundlich adsorption isotherm model compared with the Langmuir adsorption isotherm model and the adsorption kinetic data verified the best fitting with the pseudo-second-order model.